2020
DOI: 10.1016/j.heliyon.2020.e04451
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition of conserved Kadsura spp. plants in Northern Thailand

Abstract: The genus Kadsura comprises woody vine plants belonging to the family Schisandraceae . Species are found mostly in Northern Thailand and widely consumed by the local population. Occurrences of these wild fruits are rare as they only grow naturally in forest areas. Nutritive values of Kadsura spp. remain unclear, leading to improper management for food applications. Nutritional composition of Kadsura spp. was evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…It is not only consumed as food but also is highly regarded for its pharmacological properties, especially anti-HIV, anti-fungal, anti-lipid peroxidation, anti-hepatitis, anti-inflammatory, and anti-tumor properties [ 3 , 4 ]. Many studies have shown the therapeutic effects of KC such as in treating gastrointestinal disorders and rheumatoid arthritis, calming the heart, strengthening the kidneys, and promoting blood and fluid circulation [ 5 , 6 ]. It is a novel and rare species with valuable root, stem, leaf, and fruit parts used in traditional Dai medicines (TDM).…”
Section: Introductionmentioning
confidence: 99%
“…It is not only consumed as food but also is highly regarded for its pharmacological properties, especially anti-HIV, anti-fungal, anti-lipid peroxidation, anti-hepatitis, anti-inflammatory, and anti-tumor properties [ 3 , 4 ]. Many studies have shown the therapeutic effects of KC such as in treating gastrointestinal disorders and rheumatoid arthritis, calming the heart, strengthening the kidneys, and promoting blood and fluid circulation [ 5 , 6 ]. It is a novel and rare species with valuable root, stem, leaf, and fruit parts used in traditional Dai medicines (TDM).…”
Section: Introductionmentioning
confidence: 99%
“…Dibenzocyclooctadiene lignans are one of the most widely used biologically active compounds extracted from Kadsura medicinal plants in China and other Asian countries (2,38). Studies have confirmed that Kadsura medicinal plants exert various pharmacological effects, including anti-HIV, anti-fungal, anti-lipid peroxidation, anti-hepatitis, anti-inflammatory and antitumor properties, and are widely used in the treatment of rheumatoid arthritis and promoting blood and fluid circulation (39)(40)(41). Dibenzocyclooctadiene lignans have been shown to possess the potential for use in several cosmetic and pharmaceutical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritive values of fresh samples were analyzed, including energy, protein, fat, carbohydrate, fiber, sugar, ash, moisture content, vitamins (A, D, E, and C) and minerals (Ca, P, Na, K, Mg, Fe, and Zn). The standard protocols of the Association of Official Analytical Chemists (AOAC) [ 55 ] were employed according to the previous report [ 56 , 57 ]. All experiments were performed at the Institute of Nutrition, Mahidol University with the international standard for laboratory quality systems (ISO/IEC 17025:2005).…”
Section: Methodsmentioning
confidence: 99%